Pengaruh Pemanfaatan Media ICT Powerpoint terhadap Keterampilan Berpikir Kritis Siswa pada Mata Pelajaran Al-Qur’an Hadis - Mawarni, Ari; Suryana, Ermis; Fauzi, Muhammad (Fakultas Agama Islam Universitas Billfath, 2023)
The purpose of this research was to determine whether there was an effect of learning the Al-Quran Hadith based on Information Communications Technology (ICT) PowerPoint on students' critical thinking skills in the experimental class (IX.11) MTsN 2 Palembang. This study used quantitative experimental research using a Static-Group Pretest-Postest research design for 30 students in class IX.11 as an experimental class. a. In terms of the highest score in the experimental class, it was found that the highest score was 92 for 5 people with a percentage of 16.67%. b. In terms of the achievement of the lowest score, for the experimental class, it was found that the lowest score was 83 as many as 6 people with a percentage of 20%. c. In terms of success in the experimental class seen from the side of success in the moderate category with a percentage of 63.33% as many as 19 people. So it can be said that the lowest value is in the control class. In conclusion, there is a significant positive effect of learning the Al-Quran Hadith based on Information and Communications Technology (ICT) PowerPoint on the critical thinking skills of experimental class students at Madrasah Tsanawiyah Negeri 2 Palembang.